Mesenchymal Stem Cell-Derived Extracellular Vesicles and Their Therapeutic Potential. (24th August 2020) - Zhao, Ashley G.; Shah, Kiran; Cromer, Brett; Sumer, Huseyin
Abstract : Extracellular vesicles (EVs) are cell-derived membrane-bound nanoparticles, which act as shuttles, delivering a range of biomolecules to diverse target cells. They play an important role in maintenance of biophysiological homeostasis and cellular, physiological, and pathological processes. EVs have significant diagnostic and therapeutic potentials and have been studied both in vitro and in vivo in many fields. Mesenchymal stem cells (MSCs) are multipotent cells with many therapeutic applications and have also gained much attention as prolific producers of EVs. MSC-derived EVs are being explored as a therapeutic alternative to MSCs since they may have similar therapeutic effects but are cell-free. They have applications in regenerative medicine and tissue engineering and, most importantly, confer several advantages over cells such as lower immunogenicity, capacity to cross biological barriers, and less safety concerns. In this review, we introduce the biogenesis of EVs, including exosomes and microvesicles. We then turn more specifically to investigations of MSC-derived EVs. We highlight the great therapeutic potential of MSC-derived EVs and applications in regenerative medicine and tissue engineering.